PTPN11 mutations define a rare but highly adverse subset of myelodysplastic syndromes - Alexandre Bazinet; Alex Bataller; Guillermo Montalban-Bravo; Kelly Chien; Koji Sasaki; Wei Ying Jen; Mahesh Swaminathan; Tapan Kadia; Courtney DiNardo; Farhad Ravandi; Guillermo Garcia-Manero; Hagop Kantarjian (Haematologica, 2025)
Not available.